Pilihan Effektif Metode Pelaksanaan Bangunan Basement dengan Menggunakan Pendekatan Analytical Hierarchy Process (AHP) - Mansyur, Hamdani; Wahyuni, Maria; Sutianto, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
In basement construction, there are several methods that are often used in its implementation such as the top down method, bottom up and retaining wall method. However, the current popular choice in the construction industry to utilize underground space without disturbing activities on the surface is the top down method. This method involves excavation and construction of the underground floor simultaneously with the construction of the upper floor, allowing for significant time and cost savings. Focus on risk management, cost control, and safety are key aspects in implementing basement construction with the top down method. The emphasis on cost control and quality improvement is the core of value engineering in the context of construction projects. In this paper we use data analysis methods such as profit and loss analysis, matrix integral analysis and function analysis such as FAST (Functional Analysis System Technique). This analysis method is to determine the magnitude of the Eigen Value matrix and the Consistency Ratio Value. Based on the results of the analysis that has been carried out on the selection of the type of basement building construction method, it is concluded that the Top down method has advantages compared to the other 2 methods, namely bottom up and retaining walls. The cheapest cost of implementing basement construction is by using the Top down method.